Filling in the gaps: using testing and restudy to promote associative learning. Issue 9 (20th October 2016) - Bulevich, John B.; Thomas, Ayanna K.; Parsow, Charles
ABSTRACT: Although testing has been shown to potentiate subsequent learning [Izawa, C. (1966). Reinforcement-test sequences in paired-associate learning. Psychological Reports, 18, 879–919.], the mechanisms that influence this effect are not entirely understood. The present research examined the relationship between associative binding and test-potentiation effects. We hypothesised that test-potentiation effects would be most pronounced when participants could easily extract the relationship among word groupings. Towards that end, we compared three-word groupings, or triads, that were either semantically related or unrelated. Participants engaged in repeated study, repeated testing, or engaged in interpolated study and test prior to a final test. Final test performance was greatest for participants who engaged in interpolated study and test on related triads. The results support three primary conclusions: (1) testing aids in associative binding; (2) associative binding is facilitated by retrieval practice and restudy pairings; and (3) pre-existing associations facilitate test-potentiation effects.